GIS in the service of plant breeding in Karcag - Czimbalmos , Róbert; Fazekas, Mónika Éva; Murányi, Eszter; Nagy, Attila; Harangi, Attila (COLUMELLA – Journal of Agricultural and Environmental Sciences, 2022)
Plant varieties bred by the Hungarian Breeding Institutes in different agro-ecological conditions can bear the unfavourable factors of the regions with greater tolerance, so they provide advantages and yield stability for the farmers who choose from these varieties. Farmers can contribute to the genetic potential of the planted seeds with the applied cultivation technology. The stable genetical background (the high quality pre- basic, basic and certified seeds) is provided by plant breeding to the farmers. Breeding is a long and tiring task: the classical breeding process, which usually takes 8–10 years, starts with selecting variety assignments and its growing. Finally new, stable varieties are produced which can provide balanced, high yield and also have good or significant qualitative features among extreme conditions. They can bear the unfavourable conditions of the region with greater tolerance, so provide significant yield stability for the farmers. Space technology supported IT solutions (remote sensing, precision farming and soil-friendly agro-technics) has been introduced into plant breeding methods in Karcag, which greatly support the aims of breeding. The main goal is to provide harmonical growing of the nursery, the large punctuality and to decrease the number and cost of agricultural operations. In this study, the new methods and technologies applied in plant breeding in Karcag are introduced.
Keywords: site-specific plant breeding; GIS methods; remote sensing; precision farming (PF); climate change